Non-Tenured EFLTeachers’ Teaching Strategies in A Limited Face-To-Face Learning Mode - Nurmila Nurmila; Novalita Fransisca Tungka (Sintuwu Maroso Journal of English Teaching, 2022)
EFL teachers’ teaching strategies in teaching during pandemic time are crucial toexplore. This study aims to provide explanation on how the EFL high school teachers in a rural area chose and implemented their teaching strategies in a limited face-to-face learning mode. In this case study design, data were collected by interviewing, observing, and documenting two non-tenured EFL teachers’ instructional activities in North Morowali regency, Central Sulawesi. The results showed that teachers’ strategies are direct and indirect instruction, individual, and collaborative or interactive strategies. These results can be useful as a reference in the subject of teachers’ teaching strategies implementation, its effectiveness, and the influencing factors of the strategies preferences.